2012
DOI: 10.1117/1.jbo.17.6.067008
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel near infrared spectroscopy indicates regional variations in cerebral autoregulation in infants supported on extracorporeal membrane oxygenation

Abstract: Abstract. Assessing noninvasively cerebral autoregulation, the protective mechanism of the brain to maintain constant cerebral blood flow despite changes in blood pressure, is challenging. Infants on life support system (ECMO) for cardiorespiratory failure are at risk of cerebral autoregulation impairment and consequent neurological problems. We measured oxyhaemoglobin concentration (HbO 2 ) by multichannel (12 channels) near-infrared spectroscopy (NIRS) in six infants during sequential changes in ECMO flow. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Numerous experimental and clinical studies have been carried out to delineate the biological basis of optical signals obtained from healthy and injured brain. These studies present sound evidence that NIRS-derived changes in chromophore concentrations can act as markers of cerebral physiology and pathology; the results offer significant insights into the feasibility of NIRS for observation of functional activation [5,6], detection of autoregulation or metabolic failure during routine surgery or after brain injury [7,8], and assessment of impending neurological damage due to hypoxia-ischemia (HI) in adults or neonates [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental and clinical studies have been carried out to delineate the biological basis of optical signals obtained from healthy and injured brain. These studies present sound evidence that NIRS-derived changes in chromophore concentrations can act as markers of cerebral physiology and pathology; the results offer significant insights into the feasibility of NIRS for observation of functional activation [5,6], detection of autoregulation or metabolic failure during routine surgery or after brain injury [7,8], and assessment of impending neurological damage due to hypoxia-ischemia (HI) in adults or neonates [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…7 One recent study using 12-channel NIRS found regional variations of cerebral autoregulation in critically ill infants. 19 Multichannel NIRS has also been applied for perfusion measurement in adults with MCA stenosis and a delayed perfusion predominantly in the vascular border zone has been found in Ref. 20.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebral hemispheres, the diencephalons, the brain stem, and the cerebellum are four main regions of the brain [5]. An outer layer of grey matter covers the cerebral hemispheres, which is called the cerebral cortex and its thickness is approximately 5mm in adults.…”
Section: Basic Anatomy Of the Human Brainmentioning
confidence: 99%
“…But to calculate changes in concentrations of oxygenated and deoxygenated hemoglobin, the effect of scattering is negligible since it does not change over time [5,13].…”
Section: Light Scattering In Brain Tissuementioning
confidence: 99%
See 1 more Smart Citation